Tuḥfat-i islām : ḫulāṣa-i ḥālāt-i Ḥaḍrat Šaiḫ Aḫūn Ḫāǧa ʿAbd as-Salām Ṣāḥib Ḥasanī - Abū-al-Ḥasan Saiyid Muḥammad Ḥasanī al-Qādirī wa al-Čištī (Nawal Kišūr, 1915)
Biography of the 18th century Sufi Shaikh of multiple lineages, ʿAbd-as-Salām Ṣāḥib Ḥasanī (d. 1757), known as Ḥaḍrat Āḫūn Ṣāḥib